Studies towards the development of Salmonella-specific bacteriophages for sanitation in the food industry - Hobbs, Angela (My University, 2008)
ABSTRACT Bacteriophages have sparked interest as novel ways to control foodborne pathogens. The application of Salmonella-specific phages as antimicrobial agents was tested against relevant Salmonella isolates of poultry origin. Two different Salmonella-specific phages, A and C, were isolated from enriched sewage. They displayed differences in their host-range but exhibited virulent behaviour towards Salmonella enterica serovar Typhimurium ATCC 13311. Toxicity studies were conducted with individual and combined applications of phages A and C, at an MOI of 1, on Salmonella ATCC 13311. Following 3 hour exposure, both applications were equally effective at reducing Salmonella by approximately 1 x 105 CFU/ml. Similar toxicity profiles were observed with both applications, however, a delay occurred with phage A. We propose that phages A and C have similar infective specificities and that during combination competition for the receptor is overcome by phage C. Neither application eliminated Salmonella to undetectable levels. The presence of phage-resistant mutants is a fundamental issue that will hamper the use of phages as alternate antimicrobial agents.
Keywords: Salmonella; Bacteriophages